Alphaviruses in Immunotherapy and Anticancer Therapy - Kenneth Lundstrom (Biomedicines, 2022)
Alphaviruses have been engineered as expression vectors for vaccine development and gene therapy. Due to the feature of RNA self-replication, alphaviruses can provide exceptional direct cytoplasmic expression of transgenes based on the delivery of recombinant particles, naked or nanoparticle-encapsulated RNA or plasmid-based DNA replicons. Alphavirus vectors have been utilized for the expression of various antigens targeting different types of cancers, and cytotoxic and antitumor genes. The most common alphavirus vectors are based on the Semliki Forest virus, Sindbis virus and Venezuelan equine encephalitis virus, but the oncolytic M1 alphavirus has also been used. Delivery of immunostimulatory cytokine genes has been the basis for immunotherapy demonstrating efficacy in different animal tumor models for brain, breast, cervical, colon, lung, ovarian, pancreatic, prostate and skin cancers. Typically, therapeutic effects including tumor regression, tumor eradication and complete cure as well as protection against tumor challenges have been observed. Alphavirus vectors have also been subjected to clinical evaluations. For example, therapeutic responses in all cervical cancer patients treated with an alphavirus vector expressing the human papilloma virus E6 and E7 envelope proteins have been achieved.